Are Australians concerned about nanoparticles? A comparative analysis with established and emerging environmental health issues. (3rd February 2015) - Capon, Adam; Rolfe, Margaret; Gillespie, James; Smith, Wayne
Abstract: Objective: Introducing new technologies into society raises considerable public concern. We determine the public concern about nanoparticles, and compare this concern to other environmental health issues such as wind farms and coal seam gas production. Methods: A repeat cross sectional survey examining views on environmental health issues, risk, chemicals and trust was undertaken in more than 1, 300 Australian residents in 2000 and 2013. Logistic regression and principal component analysis was used to investigate predictors of nanoparticle concern and identify a component structure for environmental health issues that could explain a trend of future nanoparticle concern. Results: Australians have a relatively low level of concern about the risks of nanoparticles to health when compared to their concerns about other environmental health issues. Items associated with concern included gender, a general wish to avoid chemicals and possibly trust in politicians. Concern over nanoparticles clustered with similar views on technological risks. Conclusions: Current public concern over the risks of nanoparticles is low. However, a reframing of the issue towards 'chemicals' is likely to have a negative effect on risk perceptions. This paper raises questions about appropriate channels for the effective communication of risk.